Aktivitas Antibakteri dan Formulasi Gel Topikal Ekstrak Akar Zingiber cassumunar Roxb. Terhadap Propionibacterium acnes - Nurhasanah, Hana; Lestaria, Tresna; Rahmiyani, Ira; Virgianti, Dewi Peti (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Acne is a common inflammatory skin disorder affecting both adolescents and adults, primarily caused by the colonization of Propionibacterium acnes, which induces skin inflammation. The development of natural-based anti-acne agents may offer a safer alternative to synthetic drugs. Zingiber cassumunar Roxb. (bangle rhizome) contains flavonoids, terpenoids, saponins, and essential oils known for their strong antibacterial properties. Aim: this study aimed to evaluate the antibacterial activity of Z. cassumunar rhizome extracts against P. acnes and to formulate a topical anti-acne gel. Method: extraction was conducted using successive maceration with n-hexane, ethyl acetate, and 70% ethanol. Antibacterial activity was determined by the disk diffusion method, and gels containing n-hexane extract at concentrations of 5%, 10%, and 15% were evaluated for their physical quality. Results: the n-hexane extract exhibited the highest antibacterial activity, producing an inhibition zone of 7.56 ± 0.11 mm. The 15% extract gel (F3) showed the strongest antibacterial effect (9.26 ± 0.08 mm) and met all physical quality requirements. Conclusion: these findings indicate that the n-hexane extract gel of Z. cassumunar rhizome possesses promising potential as a natural topical formulation for treating acne caused by P. acnes.